1993
DOI: 10.1159/000463219
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Impaired Lung Function in Rubber Manufacturing Factory Workers Exposed to Benzo(d)pyrene and Respirable Particulate Matter

Abstract: The respiratory health of 726 workers in a rubber processing factory has been investigated. The values of the forced vital capacity (FVC), forced expiratory volume in 1 s (FEV(1)) and the ratio of FEV(1)/FVC in workers were inversely related to the total suspended particulate matter (TSP) and benzo(a)pyrene present in the workplace air. Statistically significant decrements in ventilatory function occurred following prolonged exposure as assessed by the duration of working in the plant. When the different secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…al. monitored the health of 667 workers working in a rubber factory 11 . Firstly, they showed that there was a negative correlation between the health of employees, and the length of employment.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…al. monitored the health of 667 workers working in a rubber factory 11 . Firstly, they showed that there was a negative correlation between the health of employees, and the length of employment.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
“…Firstly, they showed that there was a negative correlation between the health of employees, and the length of employment. Generally speaking, those employees who were employed by the factory the longest, had the poorest health 11 . Interestingly, health was also correlated to which places in the factory employees worked.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
See 1 more Smart Citation